2013
DOI: 10.1186/1471-2180-13-132
|View full text |Cite
|
Sign up to set email alerts
|

Members of the Sinorhizobium meliloti ChvI regulon identified by a DNA binding screen

Abstract: BackgroundThe Sinorhizobium meliloti ExoS/ChvI two component regulatory system is required for N2-fixing symbiosis and exopolysaccharide synthesis. Orthologous systems are present in other Alphaproteobacteria, and in many instances have been shown to be necessary for normal interactions with corresponding eukaryotic hosts. Only a few transcriptional regulation targets have been determined, and as a result there is limited understanding of the mechanisms that are controlled by the system.ResultsIn an attempt to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…Since many of these 35 regions are upstream of operons, in total we found 64 genes that are direct transcriptional targets of ChvI (Groups 1 and 2). Our findings confirm and significantly extend our previous work that identified three regions (upstream of SMc01580, ropB1 and SMb21440) directly bound by ChvI using EMSA (Chen et al, 2009), and other previous work that showed that the SMb21188-msbA2 operon is directly targeted by ChvI (Bélanger and Charles, 2013). The use of chIP, in which protein-DNA complexes are crosslinked in vivo prior to immunoprecipitation, enabled us to identify many more ChvI direct target genes compared to our previous study that relied on detecting ChvI binding in vitro (Chen et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since many of these 35 regions are upstream of operons, in total we found 64 genes that are direct transcriptional targets of ChvI (Groups 1 and 2). Our findings confirm and significantly extend our previous work that identified three regions (upstream of SMc01580, ropB1 and SMb21440) directly bound by ChvI using EMSA (Chen et al, 2009), and other previous work that showed that the SMb21188-msbA2 operon is directly targeted by ChvI (Bélanger and Charles, 2013). The use of chIP, in which protein-DNA complexes are crosslinked in vivo prior to immunoprecipitation, enabled us to identify many more ChvI direct target genes compared to our previous study that relied on detecting ChvI binding in vitro (Chen et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Previous transcriptome studies identified numerous genes that appeared to be transcriptionally regulated by ExoS/ChvI (Yao et al, 2004;Chen et al, 2009;Wells et al, 2007;Barnett and Long, 2015). However, of the ChvIregulated genes identified in those previous studies, only ropB1, SMb21440 and the SMc01580-SMc01581 operon (Chen et al, 2009) and the SMb21188-msbA2 operon (Bélanger and Charles, 2013) were shown to be directly regulated by ChvI, using EMSA to detect binding between purified ChvI protein and the upstream regions of these genes. Since mutation of ExoS/ChvI affects many genes and phenotypes, we hypothesized that many more ExoS/ ChvI direct transcriptional target genes existed, but that the in vitro conditions in EMSA did not allow their detection.…”
Section: Identification Of Direct Transcriptional Target Genes Of Chvimentioning
confidence: 93%
“…A portion of the trends that we have observed for the ⌬exoR mutant are consistent with previous studies in S. meliloti (10,15,17,56,63). However, our results expand and add to these observations, including an analysis of the effects of SCG overproduction.…”
Section: Discussionsupporting
confidence: 92%
“…Two more genes in the cell envelope category are annotated as modifiers of cell surface-associated factors: lpiA (atu2521; log 2 FC, 0.95) is involved in membrane lipid synthesis (53) and low-pH tolerance (45) in rhizobia, and glf (atu3975; log 2 FC, Ϫ1.54) is required for galactofuranose synthesis, a cell surface component in pathogens (54,55). These results are consistent with the role that ChvI plays in regulating phospholipid biosynthesis in S. meliloti (56). The appearance of these lipoproteins and cell surface-modifying genes in the expression profile suggests that the architecture of the cell envelope in exoR mutants is distinct from that of wild-type A. tumefaciens.…”
Section: Resultssupporting
confidence: 67%
“…We sought transcriptome clues as to whether this might relate to specific metabolic pathways, to energy use, or to cell envelope changes. Previous studies showed that a chvI-null mutant failed to grow on some carbon sources and that uracil or proline supplementation could generally improve its growth, suggesting that the ExoS-ChvI circuit affects carbon metabolism (49,90). Analysis of metabolic gene expression in the transcriptomes did not provide any obvious explanation for why the Ptrp-syrA plasmid enables the chvI K214T mutant to grow better on rich media.…”
Section: Figmentioning
confidence: 83%